Calcium salts as an alternative to preserve minimally processed table grape quality - Silveira Gómez, Ana Cecilia; Oyarzún, Dennise; Escalona, Víctor (Comunicata Scientiae, 2021)
The effects of calcium lactate, propionate, chloride, ascorbate and propionate (5 g L−1), combined with heat treatment (60 °C, 2 min), on the quality parameter of minimally processed table grapes, stored for 21 days at 5 °C, were investigated. Berries sanitised with NaOCl (100 mg L−1) were used as control. The respiration rate of Ca-treated berries remained below that of the control up to 17 days. No differences were found on the atmosphere composition. Firmness was maintained on berries treated with Ca until 14 days of storage, especially on the propionate and ascorbate treatments. The bound, free and total Ca measured values, were higher on Ca-treated berries. The functional quality did not show differences among the treatments. The Ca treatment combined with heat treatment, especially with the addition of ascorbate and propionate, maintained the firmness of the berries but did not show major effects on the other quality parameters evaluated.